2019
DOI: 10.1042/bcj20190136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of type 5d autotransporter phospholipases demonstrates a correlation between high activity and intracellular pathogenic lifestyle

Abstract: Autotransporters, or type 5 secretion systems, are widespread surface proteins of Gram-negative bacteria often associated with virulence functions. Autotransporters consist of an outer membrane β-barrel domain and an exported passenger. In the poorly studied type 5d subclass, the passenger is a patatin-like lipase. The prototype of this secretion pathway is PlpD of Pseudomonas aeruginosa, an opportunistic human pathogen. The PlpD passenger is a homodimer with phospholipase A1 (PLA1) activity. Based on sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…PLA 1 of VipD is dependent on Rab5 and Rab22 (Ku et al, 2012). In this study, activity characterization revealed that unlike many other PLPs, Rv3091 exhibited PLA 1 activity in addition to PLA 2 activity and did not need the participation of eukaryotic cofactors, which is consistent with the PLP AhPIA and BpPIA from the intracellular pathogens Aeromonas hydrophila and Burkholderia pseudomallei that display both PLA 1 and PLA 2 activity (Trunk et al, 2019). We failed to detect robust PLA 2 activity in Rv3091 as compared with PLA 1 activity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…PLA 1 of VipD is dependent on Rab5 and Rab22 (Ku et al, 2012). In this study, activity characterization revealed that unlike many other PLPs, Rv3091 exhibited PLA 1 activity in addition to PLA 2 activity and did not need the participation of eukaryotic cofactors, which is consistent with the PLP AhPIA and BpPIA from the intracellular pathogens Aeromonas hydrophila and Burkholderia pseudomallei that display both PLA 1 and PLA 2 activity (Trunk et al, 2019). We failed to detect robust PLA 2 activity in Rv3091 as compared with PLA 1 activity.…”
Section: Discussionsupporting
confidence: 76%
“…The PLA 1 and PLA 2 activity of purified recombinant protein (Rv3091NS, S214A, D407A, and S214AD407A) was detected using the fluorogenic phospholipid substrate [PLA 1 and PLA 2 substrates PED-A1 (Invitrogen, USA) and BODIPY PC-A2 (Invitrogen, USA)] according to the manufacturer's protocol (EnzChek Phospholipase A 1 Assay Kit and EnzChek Phospholipase A 2 Assay Kit, Invitrogen, USA) as previously described with minor modifications (Trunk et al, 2019). Briefly, the cleavage of the sn-1/sn-2 bond of PED-A1/BODIPY PC-A 2 using the PLA 1 /PLA 2 enzyme induces an increase in fluorescence emission.…”
Section: Phospholipase Assaysmentioning
confidence: 99%
“…In contrast, PlpD and its homologs appear to lack a lateral gate that might widen the dimer to allow PL-domain translocation. Curiously, a small portion of the first strand of the PlpD b-barrel binds to a lid sequence (Ile-Ser-Phe) that is similar to the last three residues of the "b-signal", a motif that is Although the exact physiological function of PlpD and its homologs is unknown, the PLdomains of PlpD and FplA (expressed without the b-barrel and POTRA domains) have been shown to bind various lipids and to have a phospholipase A1 activity that, like that of other phosphatases, is dependent on a Ser-Asp catalytic dyad [43]. Neither PlpD nor FplA, however, appears to function as a secreted virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…Neither PlpD nor FplA, however, appears to function as a secreted virulence factor. A study on the effects of purified PlpD and FlpA injected into G. mellonella larvae reported no direct toxic effects, even at very high concentrations [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation